Shiny happy people - Chapman, Clay McLeod (Delacorte Press, an imprint of Random House Children's Books, 2025)
Sixteen-year-old Kyra teams up with new boy Logan to uncover the truth behind a mysterious drug with disturbing side effects that is plaguing their town.